Job satisfaction among nurses in Cyprus - Charalambous, Andreas (My University, 2004)
Aim: The aim of this study was to explore the degree of satisfaction among nurses working in the public sector in Cyprus. Material-Method: The sample consisted of 95 members of nursing personnel working in surgical and pathological departments of all specialities operating in the Limassol General Hospital. The 95 nurses completed the survey questionnaire while 4 of them were interviewed. Results: While 45% of the staff appears either satisfied or very satisfied with their job the remaining 55% appear dissatisfied or very dissatisfied from their job. The highest levels of discontent are found with respect to the way the hospital treats nurses (50%) and for their advancement opportunities (47%). Conclusions: The majority of nurses (55%) report that they are dissatisfied with many aspects of their job. Despite, nurses' serious criticism of their working conditions they still report high levels of satisfaction for some aspects, such as the compensations and benefit scheme and the overall quality of care provided to patients. Key words: Job satisfaction, nursing staff, factors of satisfaction.
Keywords: Job satisfaction; Nursing staff; Factors of satisfaction